Simulation training to improve blood management: an approach to globalizing instruction in patient safety. (February 2014) - Sokolowski, John A; Banks, Catherine M; Hakim, Paul
In keeping with intent of this special issue—innovative ways to use modeling and simulation as an enabling technology—this paper addresses a global call for change in medical practice due to shifting populations, rising health risks, and increased expectation of governments to ensure patient safety. In advanced countries the basic economics of supply and demand are making a therapeutic commodity—blood—a costly treatment. In advancing states the rapid deformation of stored red blood cells and the prevalence of patient infection make standard transfusion medicine hazardous. As a result the World Health Organization has issued a call for alternatives to transfusion practice within the medical community. This paper introduces the implementation of patient blood management as that alternative standard of care, and it outlines an effective means to educate medical professionals via a web-based immersive simulation training tool. This tool was developed from evidence-based medicine, engineering and mathematical modeling, and simulations drawn from patient case studies. The medical instruction comprising this tool and its portability can readily serve a global audience of practitioners who are unfamiliar with these techniques and who are without an expedient means to obtain training. The tool is a multidisciplinary effort drawing on engineering, computer science, social science, and medical expertise. And just as this special issue stresses that simulation represents probably the only methodology to provide the human race with a tool for enabling control of mankind's evolution. Representing the cornerstone for anticipating future critical situations, this tool responds to an imminent dilemma in the global medical community.